Sistem Pakar Untuk Mendiagnosa Kerusakan Mesin Wet And Dry Vacum Cleaner Menggunakan Metode Certainty Factor (Studi Kasus: PT. ISS Indonesia) - Zega, Zulfan Anugerah; Nadeak, Berto; Zebua, Taronisokhi (STMIK Budi Darma, 2018)
Wet and Dry Vacuum Cleaner machines are often damaged, thus slowing down the work of cleaning service operators in completing a job. The slow technician in finding the solution of damage to Wet and Dry Vacum Cleaner machine and schedule of technicians who have been determined in two times a month to check on the condition of Wet and Dry Vacum Cleaner machine in the areas become one of the causes of inhibition of the work of cleaning service operators causing the loss on the side of time efficiency and cost incurred by the company. One solution that can be given to solve the problems being faced by PT. ISS Indonesia is utilizing an expert system-based applications. Expert system application that serves as a solution of the above problems work based on Certainty Factor method built with Microsoft Visual Studio 2008 programming language integrated with MySQL database to store data that become symptom and rules needed when doing the diagnosis by the system. This research will produce the output that is if user or user of a system does the diagnosis by choosing answer given by system through consultation form hence will yield output result of diagnosis of damage in the form of confidence level and solution of damaged machine Wet and Dry Vacum Cleaner.